The Effect of Developing an Emotional Resilience Enhancement Program to Reduce Stress in Nursing Students at Nakhon Pathom Rajabhat University - Buajaroen, Hathaichanok; Chankham, Wariya; Bungthong, Yanyong; Khaibua, Phatthamon (Journal of Ecohumanism, 2025)
Background: Stress is a mental health problem that has increasingly become more severe. Objectives: This study aimed to examine the effects of an emotional resilience enhancement program on reducing stress among students at Nakhon Pathom Rajabhat University. Methods: This study employed a quasi-experimental design. The sample consisted of 168 nursing students from the first to third years at Nakhon Pathom Rajabhat University. Data were collected using the Suanprung Stress Test-20 (SPST-20) from the Department of Mental Health. The experimental tool designed for this study was an emotional resilience enhancement program based on Grotberg's concept, comprising four activities: stress-relief podcasts, motivation-building, self-empowerment, self-encouragement, and stress-relief meditation. The research team collected data using the Suanprung Stress Test-20 (SPST-20) before and after participation in the program. The data were analyzed using Excel, and the results were evaluated using a Paired Samples t-test to compare stress levels before and after participation in the program. Results: The findings revealed that the emotional resilience enhancement program significantly reduced stress among participants, with statistical significance at the .05 level. Conclusion: The study suggests that the emotional resilience enhancement program effectively reduces stress and may be applied to students in other settings.